Students’ Perceptions of Using iPad Applications to Support EFL Oral Communication Skills - Ali Hussein Hazem; Aram George Simon; Marwa Muhammad Ahmed; Bushra Ni’ma Rashid; Bushra Saadoon Mohammed Alnoori (CV FOUNDAE, 2026)
This study aims to investigate students' perceptions of the use of iPad apps to support oral communication skills in EFL instruction. The researchers used a descriptive quantitative research design and data was collected through the use of a questionnaire to conduct this research study. A total of 30 EFL students at Secondary School in Baghdad, Iraq, were chosen at random to participate in this study during the second semester of the academic year. The questionnaire was developed to assess the perceptions of EFL students of how the use of iPad applications can assist them with speaking fluency, authentic language exposure, authentic language use, and understanding the culture of the people they are communicating with. The results of the study show that most of the students viewed the iPad applications as useful for practicing oral communication. In fact, the students indicated that the iPad applications facilitated providing them with authentic language input and making speaking activities more engaging because they had the ability to provide students with authentic language exposure. However, the students’ responses to the questionnaire also indicated that the success of using iPad applications for language practice is dependent on the effective use of pedagogical approaches and requiring the active participation of the students who are using the iPad applications for language practice. This study concludes that iPad apps have the potential to support the development of speaking skills, although more effective implementation strategies are needed in an educational setting.